Scrutinizing Coronaviruses Using Publicly Available Bioinformatic Tools: The Viral Structural Proteins as a Case Study - Beeckmans, Sonia; Van Driessche, Edilbert (Frontiers in Molecular Biosciences, 2021)
Since early 2020, the world is suffering from a new beta-coronavirus called Sars-CoV-2 that has devastating effects globally. Until today, Covid-19, which is causing life-threatening lung infections but also impairs various other organs and tissues, has been killing hundreds of thousands of people and caused irreparable damage to many others. Since the very beginning of the pandemic, huge efforts are being made worldwide to fully understand this virus and numerous studies were and still are published, many of them dealing with structural analyses of the viral spike glycoprotein and of vaccines, antibodies and antiviral molecules or immunomodulators that are assumed to become essential tools in the combat against the virus. This paper summarizes knowledge on the properties of the four structural proteins (spike protein S, membrane protein M, envelope protein E and nucleocapsid protein N) of the Sars-CoV-2 virus and of its relatives, Sars-CoV and Mers-CoV that emerged few years earlier. Moreover, attention is paid to ways to analyze such proteins using freely available bioinformatic tools and, importantly, to bring these proteins alive by looking at them on a computer screen with the easy-to-use but very performant interactive molecular graphics program DeepView. It is hoped that this paper will stimulate non-bioinformaticians and non-specialists in structural biology to scrutinize these and other macromolecules and as such will contribute to establishing procedures to fight these and maybe other forthcoming viruses.